Molecular, morphology and bioacoustic data suggest Bolivian distribution of a large species of the Leptodactylus pentadactylus group (Amphibia: Anura: Leptodactylidae) - Jansen, Martin; Schulze, Arne (Zootaxa, 2012)
During an inventory and ecological study of amphibians in the lowlands of Bolivia, we recorded two populations of a largerepresentative of the Leptodactylus pentadactylus species group (sensu Heyer 1979, 2005) formerly assigned to L.labyrinthicus. However, analyses of morphology, advertisement call, and Bayesian inference of mitochondrial DNA (16S)provided evidence for the heterospecific status in regard to L. labyrinthicus. Using an integrative taxonomic approach weherein assign these populations tentatively to L. vastus. This poses a range extension of more than 2000 km west-south-west and suggests that sampling between the known distribution areas is needed. The signal red coloration of thighs andgroin may be a diagnostic character to distinguish this species from other species of the group. Our results suggest that ataxonomic revision of the whole species group (including Bolivian populations studied herein) is needed. A far morecomprehensive sampling throughout its distribution area and further studies on species boundaries and phylogeography in this group is necessary to actually understand the taxonomy of this difficult group.